Aktivitas Antibakteri Isolat Bakteri yang Berasosiasi dengan Spons Demospongiae dari Pantai Paciran Lamongan - Oki W.D Judianti; M.M Fiqri; M.K Ansyori-KM; Guntur Trimulyono (Sains dan Matematika, 2014)
The sponges are potential to associate with bacterial isolates producing antibacterial compounds. This study was conducted toisolate and test the antibacterial activity of bacterial isolates associated with Demospongiae (Spongia sp. and Hippospongia sp.) fromPaciran Beach, Lamongan. Isolation of bacteria was done by using the pour plate method then purified by using the streak plate method.The antibacterial assay were conducted by using Escherichia coli FNCC 0091 and Staphylococcus aureus 0047 FNCC based on welldiffusion assay. There were 38 isolates of bacteria associated with sponges and two of them revealed the antibacterial activity againstE. coli FNCC 0091, while four other isolates showed antibacterial activity against S. aureus FNCC 0047. The isolates were B413, B48,B47, B410, B52, and B53. B48 has the highest antibacterial activity against E. coli FNCC 0091 and the inhibition zone diameter was37 mm, while B52 has the highest antibacterial activity against S. aureus FNCC 0047 and the inhibition zone diameter was 31 mm.